Mevalonate kinase deficiency syndrome: Single center experience - A. L. Kozlova; V. O. Bludova; V. I. Burlakov; E. V. Raykina; T. V. Varlamova; М. А. Kurnikova; А. N. Remizov; G. V. Tereshchenko; А. А. Moiseeva; S. А. Dibirova; А. L. Khoreva; А. А. Roppelt; et al. (Научно-практическая ревматология, 2021)
The aim of this study was to analyze the clinical, laboratory and molecular genetic data of 26 patients (15 boys, 11 girls) diagnosed with mevalonate kinase deficiency syndrome (MKD).Subjects and methods. The age of MKD manifestation ranged from 0 to 30.0 months (M – 1.5 months). Clinical manifestations and their severity were extremely diverse: from symptoms resembling Marshall’s syndrome to severe systemic manifestations with respiratory failure, hepatosplenomegaly and pancytopenia.Results/Conclusion. All patients had homozygous/compound-heterozygous mutations in the MVK gene, including 10 newly described variants. In all 20 patients, who have been treated with IL-1 inhibitors long enough to assess the effect of the treatment, drastic improvement of the condition was noted, but only in 17/20 patients achieved full remission.